Islands of imagination (University of Hawaiʻi Press, 2014)
Contains seven works written between 1933 and 2009. These plays are all united by the literary artistry and treatment of social issues that characterize modern Indonesian drama. Contributors include Rita Matu Mona, Armijn Pane, N. Riantiarno, Ratna Sarumpaet, Iwan Simatupang, Luna Vidya, and Putu Wijaya.